Challenges and strategies in measles vaccination: Control and eradication (Research, Society and Development, 2024)
Introduction: Since its creation in the 18th century, the vaccine has revolutionized public health, preventing 2.5 million annual child deaths, according to WHO. However, misinformation and the COVID-19 pandemic have reduced vaccination coverage, leading to the resurgence of diseases like measles, which was eradicated in Brazil in 2016 but returned in 2019. Methodology: This study is an integrative literature review, analyzing 17 articles from databases such as PubMed, SciELO, and Lilacs, with the aim of answering the question: “What are the challenges and strategies for vaccinating to eradicate and control measles in Brazil?” Results: Challenges and strategies in measles vaccination were identified, highlighting the need for effective campaigns and family health actions. Childhood vaccination is crucial for preventing outbreaks and improving public health. Discussion: Vaccine shortages, inequality in developing countries, the movement of infected individuals, and misinformation increase measles cases. Antivaccine movements and the COVID-19 pandemic have worsened the situation. Strategies like reminders and incentives could improve adherence. Conclusion: In Brazil, vaccination challenges include misinformation, notification failures, resource shortages, restricted hours, and uncontrolled immigration. Current campaigns are insufficient; more effective models need to be studied, and these challenges must be addressed. Public policies should focus on collective causes and disseminate evidence-based information.